IMMUNOGENICITY AND SAFETY OF 23-VALENT POLYSACCHARIDE PNEUMOCOCCAL VACCINE IN PATIENTS WITH RHEUMATOID ARTHRITIS: RESULTS OF A TWO-YEAR FOLLOW-UP STUDY - M. S. Naumtseva; B. S. Belov; E. N. Aleksandrova; G. M. Tarasova; A. A. Novikov; D. E. Karateev; E. L. Luchikhina; M. V. Cherkasova; Yu. V. Muravyev (Научно-практическая ревматология)
Objective: to investigate the immunogenicity, safety, and clinical efficacy of 23-valent polysaccharide pneumococcal vaccine in patients with rheumatoid arthritis (RA) during a two-year follow-up study.Subjects and methods. The prospective open-label comparative study enrolled 110 people, of them there were 81 (73.6%) women and 29 (26.4%) men at the age of 23 to 76 years, including 79 patients with RA, as well as 31 subjects without systemic inflammatory rheumatic diseases (RD) (a control group). The group of RA patients exhibited a predominance of middle-aged women who had > 3 years’ disease duration and a moderate inflammatory activity (the mean value of DAS28, 4.32). 52 patients received methotrexate (MTX), 14 had Leflunomide (LEF), and 13 were treated with tumor necrosis factor-α (TNF-α) inhibitors + MTX.The 23-valent polysaccharide pneumococcal vaccine Pneumo-23 (Sanofi Pasteur, France) was administered in a single dose of 0.5 ml subcutaneously during continuous MTX or LEF therapy for the underlying disease or 3–4 weeks before the use of TNF-α inhibitors. Clinical examinations of the patient and conventional clinical and laboratory studies were performed during control visits (1, 3, 12, and 24 months after vaccination). Clinical effectiveness and safety were evaluated in all the patients included in the study. The serum levels of anti-pneumococcal capsular polysaccharide antibodies (Ab) were measured in 72 patients with RA and in 30 individuals in the control group during a 12-month follow-up study, including in 25 patients with RA for a 24-month follow-up study by enzyme immunoassay using commercial VaccZymeTM Anti-PCP IgG Enzyme Immunoassay kits (The Binding Site Group Ltd, Birmingham, United Kingdom). Along with this, the post-immunization response coefficient was calculated for each patient as the ratio of postvaccination Ab levels during Visits 2, 3, 4, and 5 to the baseline Ab level.Results and discussion. No clinical and radiological symptoms of pneumonia were recorded in any case during the follow-up period. The patients with RA and the control group showed a more than double significant increase of anti-pneumococcal Ab level during 3 months following vaccination. Despite the decrease in their concentration by month 12, the latter remained at the appropriate level and significantly increased at 24-month follow-up. Vaccination was well tolerated. A favorable course of the postvaccinal period was noted in all cases. There were no adverse reactions to vaccination in 72 (65%) patients; 38 (35%) patients were noted to have pain, skin swelling and hyperemia up to 2 cm in diameter at the site of injection, as well as low-grade fever. There were no episodes of a RD exacerbation or any new autoimmune disorders during the follow-up period.Conclusion. The findings were suggestive of the sufficient immunogenicity and good tolerability of 23-valent pneumococcal vaccine in patients with RD during the two-year follow-up period.